Safety of Complementary and Alternative Medicine (CAM) treatment among children and young adults who suffer from adverse effects of conventional cancer treatment: A systematic review - Dana C. Mora MPH; Agnete E. Kristoffersen PhD; Grete Overvåg; Miek C. Jong PhD; Marit Mentink MSc; Jianping Liu PhD; Trine Stub PhD (Integrative Cancer Therapies, 2022)
Background: Complementary and Alternative Medicine (CAM) is widely used around the world to treat adverse effects derived from cancer treatment among children and young adults. Parents often seek CAM to restore and maintain the child’s physical and emotional condition during and after cancer treatment. Objectives: The objectives of this review were (i) to identify literature that investigates CAM use for treating adverse effects of conventional cancer treatment, (ii) to investigate the safety of the included CAM modalities, and (iii) to evaluate the quality of included studies. Methods: Five scientific research databases were used to identify observational, quasi-experimental, and qualitative studies from January 1990 to May 2021. Included studies investigated the use of CAM to treat adverse effects of cancer treatment in childhood cancer. Results: Fifteen studies were included in this review. Ten quasi-experimental, 3 observational studies (longitudinal/prospective), 2 qualitative studies, and 1 study with a quasi-experimental and qualitative arm were identified. Less than half (n = 6; 40%) of the studies included reported adverse effects for the CAM modality being studied. Among the studies that reported adverse effects, they were mostly considered as direct risk, as 13% reported mainly bleeding and bruising upon acupuncture treatment, and dizziness with yoga treatment. All adverse effects were assessed as minor and transient. CAM modalities identified for treating adverse effects of cancer treatment were alternative medical systems, manipulative and body-based therapies, biologically-based therapies, and mind-body therapies. CAM modalities were used to alleviate anxiety, pain, toxicity, prevent trauma, and improve health-related quality of life, functional mobility, and physical activity levels. All studies assessed scored 70% or above according to the Joanna Briggs Institute critical appraisal for study quality checklists. Conclusion: Most of the studies (58.3%) included in this review did not report adverse effects from CAM modalities used to treat adverse effects of cancer treatment in children and young adults. This lack of safety information is of concern because parents need to know whether the modality represents an extra burden or harm to the child. To improve awareness about safety in the field, a universal and uniform reporting system for adverse effects in CAM research is needed.